A germ-line Tsc1 mutation causes tumor development and embryonic lethality that are similar, but not identical to, those caused by Tsc2 mutation in mice - Kobayashi, Toshiyuki (The National Academy of Sciences, 2001)
Tuberous sclerosis (TS) is characterized by the development of hamartomas in various organs and is caused by a germ-line mutation in either TSC1 or TSC2 tumor suppressor genes. From the symptomatic resemblance among TS patients, involvement of TSC1 and TSC2 products in a common pathway has been suggested. Here, to analyze the function of the Tsc1 product, we established a line of Tsc1 (TSC1 homologue) knockout mouse by gene targeting. Heterozygous Tsc1 mutant (Tsc1(+/−)) mice developed renal and extra-renal tumors such as hepatic hemangiomas. In these tumors, loss of wild-type Tsc1 allele was observed. Homozygous Tsc1 mutants died around embryonic days 10.5–11.5, frequently associated with neural tube unclosure. As a whole, phenotypes of Tsc1 knockout mice resembled those of Tsc2 knockout mice previously reported, suggesting that the presumptive common pathway for Tsc1 and Tsc2 products may also exist in mice. Notably, however, development of renal tumors in Tsc1(+/−) mice was apparently slower than that in Tsc2(+/−) mice. The Tsc1 knockout mouse described here will be a useful model to elucidate the function of Tsc1 and Tsc2 products as well as pathogenesis of TS.